“Dosis de humus de lombriz y su respuesta en la producción de biomasa y rendimiento del cultivo de arroz (oryza sativa) variedad carolino bajo condiciones de secano en el fundo Miraflores de la UNSM-T en el distrito de la banda de shilcayo” - Pinchi Mori, Kiko (2007)
Paper study "OOSE OF HUMUS OF LOMBRIZ ANO RESPONSE IN THE PROOUCTION OF BIOMASS ANO PERFORMANCE IN THE CULTIVATION OF RICE (Oryza sativa), VARIETY CAROLINO UNOER CONOITIONS OF ORYLANO; whose objectives were to quantify fixing C (carbon), biomass production and yield in rice cultivation with 03 doses of abonamiento with earthworm humus. Likewise perform the economic analysis of each of the treatments. This research work was carried out in the Miraflores fundo located 3.5 kilometers Tarapoto sector Band of Shilcayo owned by the National University of San Martin. The experimental design used in this study was a design Completely Random Blocks with 5 treatments and four replicates. The parameters evaluated were to plant height, number of bunches fertile and infertile by coup, resistance to lodging, ability to macolla miento, number of days to 50% blooming size of the ear, the number of grains per ear (in va in and full) , the 1000 grain weight, incidence of pests, in kilograms per hectare yield, economic analysis and biomass produced by each of the treatment of which treatment they had doses of earthworm humus were those who gave better results in terms of production , plant height, number of grains and filled in vain, number of bunches fertile and infertile by blow, weight of 1000 grains and biomass production; you see improvements to their texture, pH, amount of M.O. Soil. As fer the cost-effective achievement was making a profit until the second round because the cost of earthworm humus not look at this application, obtaining treatment 3 (6 TM H.L) with a gain of SI. 1653.54 and treatment 1 with SI. 1430.58 respectively assuming that the residual power of the earthworm humus is an average of three years, according to research conducted in other crops.